2011
DOI: 10.1039/c1cc13731j
|View full text |Cite
|
Sign up to set email alerts
|

A melanin-inspired pro-oxidant system for dopa(mine) polymerization: mimicking the natural casing process

Abstract: An oxygen-dependent biomimetic system for DOPA, dopamine and norepinephrine polymerization exploiting the redox properties of a 5-S-cysteinylDOPA (CD)-melanin polymer is disclosed. Kinetic, chemical and scanning electron microscopy (SEM) evidence indicates conversion of DOPA into a black insoluble polymer encapsulating the active CD-melanin core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…As in the previous study (Greco et al., ), the results revealed the unexpected ability of RHP to promote the oxidative conversion of 5SCD and dopa to pigment polymers under conditions of complete exclusion of light. The differences in the conversion rate reflect the higher intrinsic oxidizability of 5SCD relative to dopa.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As in the previous study (Greco et al., ), the results revealed the unexpected ability of RHP to promote the oxidative conversion of 5SCD and dopa to pigment polymers under conditions of complete exclusion of light. The differences in the conversion rate reflect the higher intrinsic oxidizability of 5SCD relative to dopa.…”
Section: Resultssupporting
confidence: 84%
“…The potent pro‐oxidant properties of RHP toward GSH and NADH, and previous observations of the pro‐oxidant properties of synthetic CD‐mel toward catechol compounds (Greco et al., ) prompted further experiments aimed at assessing whether the natural pigment is able to promote the oxidation of melanin precursors, for example dopa and 5SCD.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, pheomelanin is formed earlier, until most cysteine and cysteine-containing peptides are consumed, and only after that eumelanin accumulates from residual dopaquinone (Simon and Peles, 2010). This is the basis for the formulation of the “casing model” of organization of the pigment granules within the melanosome (Greco et al, 2011; Ito 2006; Simon et al, 2008), with an inner pheomelanic core surrounded by the photoprotective, antioxidant eumelanic coat (Liu et al, 2005; Peles et al, 2009). It is currently unknown whether the two components are covalently linked or simply associated through non-covalent interactions.…”
Section: Nm Synthesis and Structurementioning
confidence: 99%
“…[31] Greco et al reported the spontaneous formation of core-shell melanin particles by autoxidation of DOPA in the presence of cysteinyl-DOPA melanin (CDM). [32] The CDM particle appeared to play a crucial role in DOPA oxidation and epitaxial deposition of the DM shell, and it is therefore unclear if the method could provide a general approach to DM thin film formation on other substrates. A few reports showed the in-situ formation of thin DOPA-melanin (DM) coatings on polymeric membranes to improve wettability [33,34] and to act as a primer for covalent immobilization of molecules, [3537] however in-situ grown DM films have only been shown to achieve thicknesses of 10 nm or less under conditions that typically yield much thicker films using dopamine.…”
mentioning
confidence: 99%